Utilization of mustard waste isolates for improved production of astaxanthin by Xanthophyllomyces dendrorhous - J. Tinoi (2018)
Astaxanthin production in the wild strain Xanthophyllomyces dendrorhous TISTR 5730 was investigated using different mustard waste media, including mustard waste residue extract (MRE), mustard waste residue hydrolysate (MRH), mustard waste precipitated extract (MPE), and mustard waste precipitated hydrolysate (MPH). The growth of X. dendrorhous and the production of astaxanthin were dependent on the type and initial concentrations of mustard waste media. The MPH medium was the best substrate resulting in yields of biomass and astaxanthin of 19.6 g/L and 25.8 mg/L, respectively, under optimal conditions. MPH medium improved astaxanthin production 11-fold compared to the commonly used commercial yeast malt medium, and 1.3-2.1-fold compared to other mustard waste media. © Society for Industrial Microbiology 2005.